Evolution of trappin genes in mammals - Kato, Akira (BioMed Central, 2010)
BACKGROUND: Trappin is a multifunctional host-defense peptide that has antiproteolytic, antiinflammatory, and antimicrobial activities. The numbers and compositions of trappin paralogs vary among mammalian species: human and sheep have a single trappin-2 gene; mouse and rat have no trappin gene; pig and cow have multiple trappin genes; and guinea pig has a trappin gene and two other derivativegenes. Independent duplications of trappin genes in pig and cow were observed recently after the species were separated. To determine whether these trappin gene duplications are restricted only to certain mammalian lineages, we analyzed recently-developed genome databases for the presence of duplicate trappin genes. RESULTS: The database analyses revealed that: 1) duplicated trappin multigenes were found recently in the nine-banded armadillo; 2) duplicated two trappin genes had been found in the Afrotherian species (elephant, tenrec, and hyrax) since ancient days; 3) a single trappin-2 gene was found in various eutherians species; and 4) no typical trappin gene has been found in chicken, zebra finch, and opossum. Bayesian analysis estimated the date of the duplication of trappin genes in the Afrotheria, guinea pig, armadillo, cow, and pig to be 244, 35, 11, 13, and 3 million-years ago, respectively. The coding regions of trappin multigenes of almadillo, bovine, and pig evolved much faster than the noncoding exons, introns, and the flanking regions, showing that these genes have undergone accelerated evolution, and positive Darwinian selection was observed in pig-specific trappin paralogs. CONCLUSION: These results suggest that trappin is an eutherian-specific molecule and eutherian genomes have the potential to form trappin multigenes.